A novel GTPase activated by the small subunit of ribosome - Himeno, Hyouta (Oxford University Press, 2004)
The GTPase activity of Escherichia coli YjeQ, here named RsgA (ribosome small subunit-dependent GTPase A), has been shown to be significantly enhanced by ribosome or its small subunit. The enhancement of GTPase activity was inhibited by several aminoglycosides bound at the A site of the small subunit, but not by a P site-specific antibiotic. RsgA stably bound the small subunit in the presence of GDPNP, but not in the presence of GTP or GDP, to dissociate ribosome into subunits. Disruption of the gene for RsgA from the genome affected the growth of the cells, which predominantly contained the dissociated subunits having only a weak activation activity of RsgA. We also found that 17S RNA, a putative precursor of 16S rRNA, was contained in the small subunit of the ribosome from the RsgA-deletion strain. RsgA is a novel GTPase that might provide a new insight into the function of ribosome.